Perlindungan Hukum terhadap Anak Korban Kejahatan Eksploitasi Seksual - Anisa Nurul Santi Pohan; Noor Azizah (LPPM Universitas Ekasakti Padang, 2023)
This journal discusses the Legal Protection of Child Victims of Sexual Exploitation. What is meant by child sexual exploitation is the use of children for the purpose of fulfilling sexual desires. Children as victims of criminal acts need to be protected in accordance with what is regulated in Law No. 35 of 2014 concerning Child Protection so that in the future the child is expected to be able to continue his life like children in general and no longer have the feeling that he is a victim of crime. This paper uses a juridical-empirical legal research method with a qualitative approach. The results that can be taken from this paper are that the legal protection of children as victims of sexual exploitation based on Law No. 35 of 2014 concerning Child Protection has provided legal protection in general for children as victims of crime and specifically for children who are sexually exploited.